Short-Chained Alcohols Make Membrane Surfaces Conducive for Melittin Action: Implication for the Physiological Role of Alcohols in Cells - Wang, Haoyu; Qin, Hao; Garab, Győző; Gasanoff, Edward S (Cells, 2022)
Alcohols are a part of cellular metabolism, but their physiological roles are not well understood. We investigated the effects of short-chain alcohols on Daphnia pulex and model membranes mimicking the lipid composition of eukaryotic inner mitochondrial membranes. We also studied the synergistic effects of alcohols with the bee venom membrane-active peptide, melittin, which is structurally similar to endogenous membrane-active peptides. The alcohols, from ethanol to octanol, gradually decreased the heart rate and the mitochondrial ATP synthesis of daphnia; in contrast, in combination with melittin, which exerted no sizeable effect, they gradually increased both the heart rate and the ATP synthesis. Lipid packing and the order parameter of oriented films, monitored by EPR spectroscopy of the spin-labeled probe 5-doxylstrearic acid, revealed gradual alcohol-assisted bilayer to non-bilayer transitions in the presence of melittin; further, while the alcohols decreased, in combination with melittin they increased the order parameter of the film, which is attributed to the alcohol-facilitated association of melittin with the membrane. A 1H-NMR spectroscopy of the liposomes confirmed the enhanced induction of a non-bilayer lipid phase that formed around the melittin, without the permeabilization of the liposomal membrane. Our data suggest that short-chain alcohols, in combination with endogenous peptides, regulate protein functions via modulating the lipid polymorphism of membranes.
Keywords: liposomy; lipidy; Liposomes; ERP of spin probes; melitten; mitochondrial ATP production; heart rate; non-bilayer structures; Lipids; 1H-NMR; včelí jedy; alkoholy; adenosintrifosfát; melittin; Melitten; alcohols; Bee Venoms; Adenosine Triphosphate; Alcohols